Improving the Performance of Dye-Sensitized Solar Cells - Boschloo, Gerrit (Frontiers in Chemistry, 2019)
Dye-sensitized solar cells have been investigated intensity during the last three decades. Nevertheless, there are still many aspects to be explored to further improve their performance. Dye molecules can be modified endlessly for better performance. For instance, steric groups can be introduced to slow down recombination reactions and avoid unfavorable aggregation. There is a need for more optimal dye packing on the mesoporous TiO2 surface to increase light absorption and promote a better blocking effect. Novel redox mediators and HTMs are key elements to reach higher performing DSC as they can offer much higher output voltage than the traditional triiodide / iodide redox couple.